An Analysis of Core Factors Contributing U.S – China Trade Imbalance - Ahmed, Khalid; Long, Wei (Asian Accounting and Auditing Advancement, 2013)
This paper aims to highlight the trade imbalance between the United States and China based on the analysis of core factors contributing to the imbalance. These factors are comprised of trade inequality, exchange rate issues, differences in the basic economic structure of both countries, and the methodology of calculating trade figures. This paper also highlights where both the countries differ in their point of view on their bilateral trade and why? Without a doubt, this imbalance leads the United States to face a huge deficit and China to enjoy a giant surplus in mutual trade. Now, how can we adjust the figures and narrow down the differences? The paper is also discussing the other issues which have reasonable implications for the U.S -China’s trade relations. It also enumerates the future consequences on their bilateral trade keeping in view the current scenario. The importance of this paper is further enhanced as the trade imbalance is also counted as one of the factors of the 2008 recession which is not yet fully over because there is a very slow recovery in developed countries and relatively faster in developing countries. The analysis is based on the U.S trade data from 2001 to 2010.